2012
DOI: 10.1111/j.1365-313x.2012.05126.x
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf and deformed flower1, encoding an F‐box protein, is critical for vegetative and floral development in rice (Oryza sativa L.)

Abstract: SUMMARYRecent studies have shown that F-box proteins constitute a large family in eukaryotes, and play pivotal roles in regulating various developmental processes in plants. However, their functions in monocots are still obscure. In this study, we characterized a recessive mutant dwarf and deformed flower 1-1 (ddf1-1) in Oryza sativa (rice). The mutant is abnormal in both vegetative and reproductive development, with significant size reduction in all organs except the spikelet. DDF1 controls organ size by regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…The orderly development process involves many genes and pathways that affect plant organ size by altering cell number, cell size, or both (Krizek, 2009). Although recent studies have uncovered some key regulators and genes that affect plant organ size, the intrinsic mechanisms responsible for organ size variation are yet to be fully understood (Krizek, 2009;Duan et al, 2012). In this study, we identified a PLL gene, DEL1, that appeared to play an important role in the control of organ size in rice.…”
Section: Del1 Impacts Plant Growth By Regulating Cell Cycle Progressionmentioning
confidence: 90%
See 1 more Smart Citation
“…The orderly development process involves many genes and pathways that affect plant organ size by altering cell number, cell size, or both (Krizek, 2009). Although recent studies have uncovered some key regulators and genes that affect plant organ size, the intrinsic mechanisms responsible for organ size variation are yet to be fully understood (Krizek, 2009;Duan et al, 2012). In this study, we identified a PLL gene, DEL1, that appeared to play an important role in the control of organ size in rice.…”
Section: Del1 Impacts Plant Growth By Regulating Cell Cycle Progressionmentioning
confidence: 90%
“…Cell division/expansion is a fundamental, dynamic cellular process driving plant growth and development, and it enables the plant and various organs to develop to suitable sizes (Duan et al, 2012). The orderly development process involves many genes and pathways that affect plant organ size by altering cell number, cell size, or both (Krizek, 2009).…”
Section: Del1 Impacts Plant Growth By Regulating Cell Cycle Progressionmentioning
confidence: 99%
“…Many rice mutants associated with the vegetative development and floral organ identity have been obtained such as apo1, sad1, opb, afd1 , and ddf1 (Ikeda et al, 2007; Horigome et al, 2009; Duan et al, 2012; Ikeda-Kawakatsu et al, 2012; Li et al, 2015; Ren et al, 2016b). However, our understanding of vegetative and reproductive development in rice remains limited, and the discovery of more rice mutants will further our knowledge of the regulatory mechanism behind these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lateral growth of the lemma and palea was suppressed and the resulting structure was unable to enclose the inner floral organs (Horigome et al, 2009). Dwarfism occurred in the afd1 and ddf1 mutants due to defects in cell proliferation and expansion and the lodicules and stamens were transformed into glume-like organs (Duan et al, 2012; Ren et al, 2016b). The genes responsible for these phenotypes are expressed in all tissues and organs, suggesting that these genes are not tissue-specific and play important roles in the regulation of whole-plant development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation